(untitled) (Research, Society and Development, 2022)
Aphthoid lesions comprise a group of diseases characterized by single or multiple, painful, superficial ulcerations located on the oral mucosa. A typical aphthoid lesion is small, round or ovoid, with circumscribed margins, erythematous halo, and a pale or yellowish background. This study aimed to review the literature on aphthoid lesions of the oral mucosa, highlighting their clinical presentation, diagnosis and treatment, as well as the importance of a correct clinical management in patients who have such lesions in the oral cavity. For the construction of this work, a bibliographic survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley reference manager. Scientific studies available in the literature report that there are various aphthoid lesions that affect the oral cavity. These cases involve recurrent aphthous stomatitis, Behçet’s disease, systemic lupus erythematosus, mucosite and chemical burn. These injuries can harm the quality of life of patients who present complaints of discomfort from these injuries. Therefore, it becomes essential that health professionals are familiar with these disorders, once these oral lesions can serve as fundamental indicators of early diagnosis of disease.